Bridging Law and Practice in Systematic Complete Land Registration (PTSL): A Juridical Analysis of the National Land Agency's Authority - Zetria Erma; Said Rizal; Elvira Fitriyani Pakpahan; Heriyanti; Roswita Sitompul (PT. Islamic Research Publiser, 2026)
Systematic Complete Land Registration (Pendaftaran Tanah Sistematis Lengkap/PTSL) constitutes a strategic legal instrument introduced by the Indonesian government to accelerate nationwide land registration while strengthening legal certainty, protecting property rights, and improving land governance. Despite its ambitious objectives, the implementation of PTSL continues to encounter institutional, administrative, and socio-legal challenges that affect the effectiveness of the National Land Agency's (Badan Pertanahan Nasional/BPN) authority in translating legal mandates into practice. This study aims to examine the legal authority of the National Land Agency in implementing PTSL, evaluate the gap between regulatory provisions and field implementation, and identify the principal factors influencing the effectiveness of the program. Employing an empirical juridical field research design with a socio-legal approach, this study collected primary data through semi-structured interviews with officials responsible for PTSL implementation within the National Land Agency, complemented by observations and document analysis. Secondary data were obtained from statutory regulations, government policies, scholarly literature, and relevant legal documents. Data were analyzed qualitatively using an interactive model involving data reduction, categorization, interpretation, and triangulation to ensure the validity and reliability of the findings. The results demonstrate that although the National Land Agency possesses a comprehensive legal mandate under the prevailing regulatory framework, practical implementation remains constrained by limited public awareness, financial burdens associated with taxation and administrative costs, inadequate boundary demarcation, low institutional trust, and insufficient budgetary support from both central and local governments. The study further reveals that inter-institutional coordination, community engagement, and adaptive public communication significantly enhance the effectiveness of PTSL implementation. This research contributes to the development of land law scholarship by bridging the normative framework of administrative authority with empirical implementation, offering recommendations for strengthening institutional governance, improving regulatory effectiveness, and promoting sustainable legal certainty in Indonesia's national land registration system.